Medical and hygienic means of prevention of generalized periodontal diseases in patients with manifestations of anxiety - Horodnov Є. В. (Actual Dentistry, 2024)
The purpose of the study: to investigate and substantiate the choice of medical and hygienic means (toothpastes) for the prevention of dystrophic-inflammatory periodontal diseases. Research materials and methods. The object of the study was 157 patients with generalized periodontitis associated with manifestations of anxiety, aged 35–55 years, the gender composition of patients—men (28.7%), women (71.3%). Research results. It was established that during the clinical examination of the oral cavity using the Green-Vermillion hygiene index, RI and RMA, the indicators had a satisfactory, unsatisfactory and poor state of hygiene. For the purpose of treatment and prevention, it was suggested to use toothpastes. Parodontax Complex Protection paste was chosen by 30 women and 11 men who were included inthe GP-“P” group; Lacalut fitoformula paste was used by 35 women and 8 men, whom we included in the GP-“L” group; 31 women and 12 men were identified from Colgate Total 12 Medicinal Herbs and were included in the GP-“C” group. Preventive measures of the oral cavity with toothpastes lasted 6 weeks. After that, the effectiveness of Parodontax Complex Protection, Lacalut fitoformula, and Colgate Total 12 Medicinal Herbs pastes were determined. Also, using a questionnaire, the use of toothbrushes and mouth rinses was investigated. Conclusion. It was found that the studied toothpastes Parodontax Complex Protection, Colgate Total 12 Medicinal herbs, and Lacalut fitoformula showed high efficiency of use, which is proven by the results of dynamics and explained by the composition of plant components. According to our research, the Parodontax Complex Protection toothpaste turned out to be a more effective preventive measure. Based on this, it is advisable to recommend it in the maintenance phase of complex treatment of inflammatory periodontal diseases in patients associated with manifestations of anxiety.